Design and Testing of β-Actin Primers for RT-PCR that Do Not Co-amplify Processed Pseudogenes - T. Raff; M. van der Giet; D. Endemann; T. Wiederholt; M. Paul (BioTechniques)
Quantitative reverse transcription polymerase chain reaction (RT-PCR) is being used increasingly as an alternative to Northern blots analysis or RNase protection assays for quantitation of gene expression. To quantify different samples, measurements are often normalized using the expression of so-called “housekeeping” genes, such as cytoplasmic β-actin or glyceraldehyde-3-phosphate dehydrogenase. This approach can produce false results because the presence of processed pseudogenes in the genome, which are related to some of the commonly used transcripts of housekeeping genes, leads to coamplification of contaminating genomic DNA. By yielding amplification products of the same or similar size as the reverse-transcribed target, mRNA quantitation of expression is prone to error. In this paper, we report the results of using three sets of β-actin primers for RT-PCR in the presence and absence of genomic DNA. In addition, we propose two new pairs of oligonucleotide primers that specifically amplify the human and rat β-actin reverse-transcribed mRNA but not pseudogene sequences. These primers are especially suitable for quantitation of mRNA in small tissue samples (e.g., biopsies), where DNase digestion is not feasible, and therefore DNA contamination cannot be avoided.